Rewrite each expression as a radical in simplest form: I need help!
We are using this property, GM
a(m/n) = n√[am ]
Also remember that am / a n = a (m - n )
We just need to be careful about the term that the exponent is applied to
a) 4x1/2 = 4 * x1/2 = 4 * 2√ [ x1 ] = 4 √x
Note that the exponent doesn't apply to the 4 !!!!
b) (4x)1/2 .....note that the exponent applies to (4x)....this is different from the first one...=
√[4x ] = 2√x
c) Note x -a = 1 / xa
x-2/5 = 1/ x2/5 = 1 / 5√[ x2 ]
d) Note that (8x3)1/3 = 81/3 * (x3)1/3 = 3√8 * x1 = 2x1
____ = x (2/3 - 1) = x-1/3 = 1 / x1/3 = 1 / 3√x
____ can you finish this one, GM ?????